Assessment of the Soil Structure Inertial Interaction Effect on the Behavior Coefficient Using Simplified Methods - Attia, A.; Hadji, T. (Engineering, Technology & Applied Science Research, 2022)
This study aims to assess the effect of the Soil Structure inertial Interaction (SSI) on the behavior coefficient (R). For this purpose, R was estimated with and without SSI. The pushover N2 method and its extension SSI-N2 method were applied to the plain Reinforced Concrete (RC) frame structures. For calculating the SSI effect on R, four shear wave velocities Vs, representing rocky soil, firm soil, loose soil, and very loose soil, with three soil damping ratios ζg% for each soil type were considered. The estimated values of R using the N2 method were 4.1, 4.97, 5.75, and 6.96 for rocky soil, firm soil, loose soil, and very loose soil respectively. For the SSI-N2 method, R values were in the range of 3.67-3.97 for rocky soil, 4-4.69 for firm soil, 4.01-5.09 for loose soil, and 4.14-5.81 for very loose soil. In the Algerian code, R was kept constant for each soil type, and its value is 3.5 and 5 with and without infill masonry respectively. Soil shear wave velocity and the soil damping ratio must be taken into account in calculating R. The redundancy, overstrength, and ductility reduction coefficients were determined by taking into account the SSI. The SSI effect can change the values of R, so it must be taken into account when calculating R.